2019
DOI: 10.31407/ijees9219
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Chitosan From Shrimp Skin and Operating It With Edta and Used in the Removal of Heavy Metals of Water

Abstract: The use of bio-polymers due to bio-degradability and low cost has been considered for the removal of heavy metals from water and wastewater. Chitosan polymer is a hydrophilic Cation that removes acetyl ketamine from the alkaline environment and is widely used as a sorbent for the removal of heavy metals. Chitosan is a biopolymer that has been widely used in a variety of fields, such as bio-medicine, water purification and food industries, due to its low prices and biological properties, such as biodegradabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It seems that the proposed mechanism was based on the diffusion and intraparticle layer effects. (Mozaffari et al (2019) presented an SEM image of ZnO/MnO 2 nanocomposites (Figure 6), which can be synthesized by hydrothermal method for Pb 21 adsorption. Their results showed that the maximum removal was 99% for 10 mg L 21 of Pb 21 concentration.…”
Section: Pigment and Resin Technologymentioning
confidence: 99%
“…It seems that the proposed mechanism was based on the diffusion and intraparticle layer effects. (Mozaffari et al (2019) presented an SEM image of ZnO/MnO 2 nanocomposites (Figure 6), which can be synthesized by hydrothermal method for Pb 21 adsorption. Their results showed that the maximum removal was 99% for 10 mg L 21 of Pb 21 concentration.…”
Section: Pigment and Resin Technologymentioning
confidence: 99%